Breastfeeding and COVID-19 vaccination: position statement of the Italian scientific societies - Riccardo Davanzo; Massimo Agosti; Irene Cetin; Antonio Chiantera; Giovanni Corsello; Luca A. Ramenghi; Annamaria Staiano; Marcello Tavio; Alberto Villani; Elsa Viora; Fabio Mosca (BMC, 2021)
Abstract The availability of a COVID-19 vaccine has raised the issue of its compatibility with breastfeeding. Consequently, the Italian Society of Neonatology (SIN), the Italian Society of Pediatrics (SIP), the Italian Society of Perinatal Medicine (SIMP), the Italian Society of Obstetrics and Gynecology (SIGO), the Italian Association of Hospital Obstetricians-Gynecologists (AOGOI) and the Italian Society of Infectious and Tropical Diseases (SIMIT) have made an ad hoc consensus statement. Currently, knowledge regarding the administration of COVID-19 vaccine to the breastfeeding mother is limited. Nevertheless, as health benefits of breastfeeding are well demonstrated and since biological plausibility suggests that the health risk for the nursed infant is unlikely, Italian scientific societies conclude that COVID-19 vaccination is compatible with breastfeeding.